2017
DOI: 10.37358/rc.17.8.5781
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Effects of Some Tyrosine Kinase Inhibitors on Pro-B Cells-Induced Apoptosis

Abstract: The present studies aimed the effects of tyrphostin AG 494 and tyrphostin AG 1295 on apoptosis of mouse pro-B lymphocytes. The actual scientific literature lacks such data. Tyrphostin AG 494 is an inhibitor of epidermal growth factor receptor pathways and tyrphostin AG 1295 is an inhibitor of platelet-derived growth factor receptor pathways. Our obtained data demonstrated that tyrphostin AG 1295 was less effective in preventing the apoptosis of murine pro-B cells, triggered by the combination of Cytoporone B (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…According to the literature data, stable emulsions involve particle sizes below the limit of 500 nm and the PDI below the value of 0.3 [ 44 , 45 ]. The prepared particles in this study have dimensions under 300 nm and the zeta potential can be varied from negative to positive one, based on the anionic/cationic character of the core emulsion and the polymers added on the surface: hyaluronic acid-negative one and chitosan-positive one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature data, stable emulsions involve particle sizes below the limit of 500 nm and the PDI below the value of 0.3 [ 44 , 45 ]. The prepared particles in this study have dimensions under 300 nm and the zeta potential can be varied from negative to positive one, based on the anionic/cationic character of the core emulsion and the polymers added on the surface: hyaluronic acid-negative one and chitosan-positive one.…”
Section: Discussionmentioning
confidence: 99%
“…Based on reaction time, an irritation score (IS) is calculated (Table 2). The time (s) of onset was noted for each of the irritating effects (hemorrhage, hyperemia and coagulation) [76] and the irritation potential (IS) was calculated using the following Equation (45) [77,78]:…”
Section: In Vitro Tests For Ocular Tolerabilitymentioning
confidence: 99%
“…For the complete development of the experimental plan, another cell line, pro-B lymphocyte type, dependent on interleukin (IL)-1, was used. For the multiplication of these cells in culture, Roswell Park Memorial Institute (RPMI) 1640 medium was used, also supplemented with L-Glutamine, Penicillin, and Streptomycin (antibiotics), decomplemented 10% FBS, and, last but not least, 5% CO2 (but also 37oC) [ 9 ]. A series of preliminary studies demonstrated that this cell line was surface positive for calnexin, but not for CD19-type molecules, thus proving that they did not belong to pre-B lymphocyte cell lines (flow cytometry).…”
Section: Methodsmentioning
confidence: 99%
“…A series of preliminary studies demonstrated that this cell line was surface positive for calnexin, but not for CD19-type molecules, thus proving that they did not belong to pre-B lymphocyte cell lines (flow cytometry). The viability of pro-B lymphocytes, when exosomes derived from gingival fibroblasts were present (exosomes+) or absent (exosomes-) from the culture medium of this cell type, was quantified using Trypan Blue (0.2%) and phase contrast microscopy (Nikon Eclipse TE300) [ 9 ]. In order to experimentally evaluate the apoptosis of pro-B type lymphocytes, induced as a result of the known activation of NR4A1-type orphan receptors [10 μM Cytosporone B (Csn-B)], in the presence or absence of exosomes derived from gingival fibroblasts, we administered as a treatment: 1 μM R-7050 [functional inhibitor of tumor necrosis factor alpha (TNFα)], 1 μM Z-IETD-FMK (functional inhibitor of caspase 8), 1 μM GSK690693 (functional inhibitor of Akt 1/2/3 pathways) and, last but not least, 1 μM scutellarin [functional inhibitor of receptor activator of nuclear factor-kappa B ligand (RANKL)] and therefore of the signal transducer and activator of transcription 3 (STAT3) pathway.…”
Section: Methodsmentioning
confidence: 99%
“…All experimental studies were performed in the light of the uniformly accepted ethical principles stated by the Helsinki Declaration [25][26][27][28][29][30][31].…”
Section: Experimental Partmentioning
confidence: 99%